Análise topológica experimental por perfilometria cíclica indutiva de superficies de paredes estruturais - Costa, Christiano Jose Menezes da (2013)
To enhance the maintenance practices, Oil and Gas Pipelines are inspected from the inside by automated systems called PIG (Pipeline Inspection Gauge). The inspection and mapping of defects, as dents and holes, in the internal wall of these pipelines are increasingly put into service toward an overall Structural Integrity Policy. The residual life of these structures must be determined such that minimize its probability of failure. For this reason, the investigation on the detection limits of some basic topological features constituted by peaks or valleys disposed along a smooth surface is of great value for determining the sensitivity of the measurements of defects from some combinations of circumferential, axial and radial extent. In this investigation, it was analyzed an inductive profilometric sensor to scan three races, radius r1, r2, r3, in a circular surface of low carbon steel, equipped with eight consecutive defects simulated by bulges and holes by orbit, equally spaced at p/4 rad. A test rig and a methodology for testing in laboratory were developed to evaluate the sensor response and identify their dead zones and jumps due to fluctuations as a function of topological features and scanning velocity, four speeds different. The results are presented, analyzed and suggestions are made toward a new conception of sensor topologies, more sensible to detect these type of damage morphologies